Feasibility and Outcome of Routine Use of Concurrent Chemoradiation in HIV-positive Patients With Squamous Cell Anal Cancer. (October 2020) - Leiker, Andrew J.; Wang, Chiachien J.; Sanford, Nina N.; Aguilera, Todd A.; Karri, Sirisha; Beg, Muhammad S.; Kazmi, Syed A.; Olson, Craig; Matthews, Joselin A.; Abdelnaby, Abier; Meyer, Jeffrey J.; Folkert, Michael R.
Abstract : Objectives: Clinical concerns about hematologic toxicities in human immunodeficiency virus (HIV)+ patients with squamous cell anal cancer (SCAC) may lead to de-escalation of treatment intensity. The objective of this study is to evaluate clinical outcomes including toxicity following standard concurrent curative-intent chemoradiation for HIV+ and HIV− patients with SCAC. Materials and Methods: Among 97 evaluable patients treated between 2009 and 2016 (median age 52.2 y), 43 (44.3%) were HIV+ and 54 (55.7%) HIV−. The majority of the radiation was delivered using intensity-modulated radiation therapy and chemotherapy consisting primarily (93%) of 5-fluorouracil and mitomycin C. Clinical outcomes assessed included toxicity, locoregional control (LRC), distant metastasis (DM), progression-free survival (PFS), colostomy-free survival (CFS), overall survival (OS), and cause-specific survival (CSS). Results: With a median follow-up of 45 months, HIV+ patients exhibited a trend toward reduced OS compared with HIV− patients (4 y OS 61.2% vs. 78.3%; HR 2.09; 95% CI, 0.97-4.52; P =0.055) on univariable analysis, but HIV status was not significant after adjusting for additional parameters on multivariable analysis. Toxicity rates, LRC, CFS, PFS, freedom from DM, and CSS were similar between the 2 cohorts. On multivariable analysis, tumor size >5 cm impacted all clinical outcomes (trend for LRC) except CFS. Radiation treatment extension beyond 7 days was found to negatively impact LRC and CSS. Male sex was associated with worse CFS. Conclusions: Radiation therapy with concurrent 5-fluorouracil and mitomycin C chemotherapy is reasonably well-tolerated as curative treatment for HIV+ patients with SCAC, and no significant difference in outcomes was noted relative to HIV− patients. Abstract : Supplemental Digital Content is available in the text.